The role of plant hormones on the reproductive success of red and brown algae - Uji, Toshiki; Mizuta, Hiroyuki (Frontiers in Plant Science, 2022)
Seaweeds or macroalgae are important primary producers that serve as a habitat for functioning ecosystems. A sustainable production of macroalgae has been maintained by a diverse range of life cycles. Reproduction is the most dynamic change to occur during its life cycle, and it is a key developmental event to ensure the species’ survival. There is a gradually accumulating evidence that plant hormones, such as abscisic acid and auxin, have a role on the sporogenesis of brown alga (Saccharina japonica). Recent studies reported that 1-aminocylopropane-1-carboxylic acid, an ethylene precursor, regulates sexual reproduction in red alga (Neopyropia yezoensis) independently from ethylene. In addition, these macroalgae have an enhanced tolerance against abiotic and biotic stresses during reproduction to protect their gametes and spores. Herein, we reviewed the current understanding on the regulatory mechanisms of red and brown algae on their transition from vegetative to reproductive phase.